2018
DOI: 10.1097/shk.0000000000000941
|View full text |Cite
|
Sign up to set email alerts
|

Improving Patient Selection for Refractory Out of Hospital Cardiac Arrest Treated with Extracorporeal Life Support

Abstract: The use of a new paradigm of ROHCA dramatically shortened the time to ECLS initiation by reducing the time spent on site by more than 20 min. Survival improved from 7% to 25% after implementation of OSCAR-ECLS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…These findings are consistent with a recent study demonstrating an improved outcome after implementation of a standardized ECPR protocol at a single center. 41 Furthermore, a recent RCT on ECPR vs. CCPR (ARREST trial) demonstrated that early initiation ECMO resulted in an impressive 43% survival to hospital discharge for refractory shockable rhythm. Despite the small sample size, the study demonstrated that ECPR care in an experienced centre with expertise, and streamlined ECPR protocols and transport system can dramatically improve survival and neurological outcome.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with a recent study demonstrating an improved outcome after implementation of a standardized ECPR protocol at a single center. 41 Furthermore, a recent RCT on ECPR vs. CCPR (ARREST trial) demonstrated that early initiation ECMO resulted in an impressive 43% survival to hospital discharge for refractory shockable rhythm. Despite the small sample size, the study demonstrated that ECPR care in an experienced centre with expertise, and streamlined ECPR protocols and transport system can dramatically improve survival and neurological outcome.…”
Section: Discussionmentioning
confidence: 99%
“…After excluding the duplicated papers, review or meeting abstracts, and irrelevant articles, 60 articles were left for further screening by checking the full texts. 47 articles were excluded, of which, seven were overlapped studies [42][43][44][45][46][47][48], seven were performed in pediatric patients [49][50][51][52][53][54][55], two study contained patients with other disease besides CA and the data related to CA could not be obtained separately [16,56], three studies contained CA patients treated with other methods besides ECPR and the data related to ECPR could not be obtained separately [17,57,58], fifteen studies had no sufficient data [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73], and eleven studies only had therapeutic hypothermia arms (without controls) [37,[74][75][76][77][78][79][80][81][82][83]. Two...…”
Section: Discussionmentioning
confidence: 99%
“…Allein durch die Tatsache, dass strukturiert vorgegangen, also ein Standard oder Protokoll verwendet wird, und dass eine rigorose Patientenauswahl erfolgt, können Prozesszeiten verbessert und Überlebensraten gesteigert werden [3,6,9]. Auch hier ist bezüglich der Vergleichbarkeit von Daten jedoch anzumerken, dass die Endpunkte in der Literatur unterschiedlich definiert sind, und mit Überlebensrate nicht immer nur neurologisch günstiges Überleben gemeint ist, was eine Interpretation erschwert.…”
Section: Welche Patienten Kommen Für Ecpr In Frage Und Welche Nicht?unclassified